Optimalisasi Digitalisasi Pemasaran Melalui Media Sosial Untuk Meningkatkan Daya Saing UMKM Mindari Kupang - Ban, Novemli Ola; Langging, Yanuarlus Sinta Susanti; Idor, Simforianus; Mari, Memito Marianus; Koloman, Chrismastiana; Jando, Emanuel (Lembaga Dongan Dosen, 2025)
Mindari Kupang MSMEs face challenges in increasing visual appeal and engagement on Instagram, which has resulted in low product sales. This study aims to evaluate the effectiveness of changes to the Instagram feed design of Mindari Kupang MSMEs in increasing engagement and sales. The method used is Action Research, which involves the stages of diagnosis, planning, implementation, evaluation, and learning. The results show that a consistent feed design with a harmonized color palette and typography can increase follower engagement as well as the perception of content relevance. Evaluation through questionnaires showed significant improvements in visual impression and the effectiveness of the design in conveying information. The conclusion of this study shows that strategically redesigning Instagram feeds can increase engagement and sales, and provide insights for other MSMEs in optimizing digital marketing through social media.